2005
DOI: 10.1158/1078-0432.ccr-05-0001
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Interleukin-6 Gene Polymorphisms and the Risk of Breast Cancer in Caucasian Women

Abstract: Purpose: Genetic polymorphisms of cytokine-encoding genes are known to predispose to malignant disease. Interleukin (IL)-1 and IL-6 are crucially involved in breast carcinogenesis. Whether polymorphisms of the genes encoding IL-1 (IL1) and IL-6 (IL6) also influence breast cancer risk is unknown. Experimental Design: In the present case-control study, we ascertained three polymorphisms of the IL1gene cluster [À889 C/T polymorphism of the IL1a gene (IL1A), À511C/T polymorphism of the IL1b promoter (IL1B promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 40 publications
4
64
2
1
Order By: Relevance
“…Our results showed that the prevalence of the CC genotype was significantly higher among the cancer patients. These findings are consistent with Hefler et al (2005), who also observed a higher incidence of the CC genotype among Caucasian women with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that the prevalence of the CC genotype was significantly higher among the cancer patients. These findings are consistent with Hefler et al (2005), who also observed a higher incidence of the CC genotype among Caucasian women with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to numerous other mechanisms, involvement of cytokines in the progression and pathogenesis of cancer has been observed in various patient cohorts (Smyth et al, 2004;Pooja et al, 2012). For instance, the cytokines interleukin (IL)-1, IL-4, IL-6, and IL-10 are important biomarkers for breast cancer pathogenesis and prognosis (Hefler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary factors that influence cytokine expression levels is genetic variation or gene polymorphisms. Cytokine gene polymorphisms have been linked to cancer susceptibility and severity (Hefler et al, 2005), and to physiological responses to cancer treatment (Andreassen et al, 2005). To determine whether differences in single nucleotide polymorphisms (SNPs) might contribute to persistent post-treatment fatigue, we recently examined SNPs in the promoter regions of 3 cytokine genes [IL-1β -511 (T/C), IL-6 -174 (G/C), and IL-6R -183 (G/A)] in fatigued and nonfatigued breast cancer survivors (Collado-Hidalgo et al, 2007).…”
Section: Risk Factors For Inflammation and Fatiguementioning
confidence: 99%
“…A single nucleotide polymorphism (SNP), named rs1800795 (consisting of a G → C transversion in position −174 from the transcription start site) located in the promoter region of the IL-6 gene (NM_000600) reduces IL-6 production at the transcriptional level (Fishman et al 1998). The presence of the rs1800795 C-allele has been associated with a mild phenotype of inflammation-triggering pathologies (Hefler et al 2005, Sawczenko et al 2005. The role of rs1800795 in longevity has been explored in the Italian population with conflicting results (Bonafè et al 2001;Capurso et al 2004;Christiansen et al 2004;Hurme et al 2005).…”
Section: Introductionmentioning
confidence: 99%